AsSee：assistive mobile application for visual impaired individual - Lim, Wei Hao (2024)
The numbers of visually impaired individuals increase year by year but in this era of developing rapidly, the mobility and safety of visual impaired individuals issue during travel raised due to unfriendly environments and limited information about the surrounding of the environment. There are numbers of assistive technology ready to assist them in different perspectives, but the price which is not affordable for majority of the visual impaired individual and required extra equipment to take advantage of the assistive technology. Therefore, there is a need of assistive mobile application for visual impaired individuals to assist them in gather information of the environment and feedback to them accurately for better understanding of the environment and decisions making. Furthermore, the usage of the paper and documentation in most of the procedures in daily lifes where is a big challenges for them to understand written documents and texts in not in braille without any assistance which lead to need of application that helps user to capture written texts and convert into speech to let them gain understanding and information on the paper is important where could assist them in daily life activities and in some important procedures. In conclusion, this project aims to provide a mobile application to assist user in real-time environment object detection to assist them gather information of the environment and the text recognition and convert to speech for them accessible to the information of written text.